TEKS GEGURITAN I JAPATUAN SEBAGAI WUJUD ASIOLOGIS RELIGIUS SOSIOBUDAYA MASYARAKAT BALI HINDU - Watra, I Wayan; Ayu Mudiasih, I Gusti (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 16 (2009): March 2009, 2009)
Abstract Speaking about geguritan mean to discuss one of the loaded belleslettres warehouse with symbol, meaning, sociology, cultural, religion value, and say to lead human being to have ethics. Belleslettres in the form of extant geguritan of lilting poem, which is edenticed with Javanese song. Geguritan Japatuan is contented context and text; symbol, meaning, religion value offers by writer which is later; then referred as word. Problem pf able to be lifted by is: (1). How descriptive form, narasi, and argument of exposition Geguritan Japatuan? (2) acting to say its bearing with context, act locution, ilokusi, and perlokusi?(3). How Meaning say text of Geguritan Japatuan?